The Pemberdayaan Masyarakat Dalam Penanganan Balita Stunting Melalui Pemanfaatan Pangan Lokal Berbasis Singkong Di Kelurahan Bandarraya - Jesi, Jesi Alexander Alim; Purba, Anita Pranawasari; Manurung, Jesika Yolanda; Aritonang, Okto Ijen; Mardita, Meza (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Bandarraya Village is one of the villages that is a priority for stunting handling by the Bandarraya kukerta team. Stunting intervention can be done through the use of local food sources of carbohydrates such as cassava. The purpose of this activity is to increase public knowledge about the potential of local food and to produce local food products that can be utilized in the prevention and control of stunting in Bandarraya Village. The expected targets of this activity are increasing public knowledge about stunting awareness, increasing community participation in empowering local potentials for improving nutrition, and producing cassava-based food products that can be used as additional food for toddlers. Methods of implementing mentoring activities. The results achieved in this activity were that the Kukerta Bandarraya students and the community knew stunting, the causal factors, understood local food sources related to stunting prevention, were able to produce products in the form of compote and formed a group of PKK mothers who independently practiced making compote implemented in Posyandu activities. This Bandarraya kukerta work program activity received great support from the ranks of the sub-district and sub-district areas